CFD study on syngas dispersion for biomass process industry - Ab Kadir, N.A. (Trans Tech Publications Ltd, 2014)
Synthesis gas (syngas) refers to a mixture primarily of hydrogen (H2) and carbon monoxide (CO) which may also contain significant but lower concentrations of methane (CH4) and carbon dioxide (CO2) as well as smaller amounts of impurities such as chlorides, sulphur compounds, and heavier hydrocarbons. Available syngas dispersion study found in literatures mostly focused on pure gas dispersion specifically H2 compared to the syngas mixture. It has been reported in most literatures that available commercial tools tend to give an overestimated results for these types of gas since it is more suitable for dense gas rather than the light gas. Therefore, the current study aim to investigate potential dispersion and evaluate the flammability of syngas release from biomass processes using CFD-FLUENT. Results of the mixture simulation is compared with the results obtain from simulation of pure H2 release. When all components in syngas were release together, competition to gain oxygen increased resulting in lesser mixing of syngas-oxygen and increasing the concentration of the syngas mixture. As a result, H2 in syngas concentration is higher compared to pure H2 when accidental release from biomass process. Â© 2014 Trans Tech Publications, Switzerland.